2004
DOI: 10.1038/sj.onc.1208110
|View full text |Cite
|
Sign up to set email alerts
|

Magicin, a novel cytoskeletal protein associates with the NF2 tumor suppressor merlin and Grb2

Abstract: Neurofibromatosis 2 (NF2) is a dominantly inherited disorder characterized by bilateral vestibular schwannomas and meningiomas. Merlin, the neurofibromatosis 2 tumor suppressor protein, is related to the ERM (ezrin, radixin, moesin) proteins and, like its family members, is thought to play a role in plasma membrane-cytoskeletal interactions. We report a novel protein as a merlin-specific binding partner that we have named magicin (merlin and Grb2 interacting cytoskeletal protein) and show that the two proteins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 44 publications
3
61
0
Order By: Relevance
“…The anti-WAVE, anti-N-WASP, and anti-WIP antibodies have been described (13,16,17). Anti-NHE-RF IC270 and anti-merlin antibodies 1C4 and C26H were described previously (18,19). Anti-Nck and anti-Myc 9E10 antibodies were purchased from BD Transduction Laboratories and Developmental Studies Hybridoma Bank, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The anti-WAVE, anti-N-WASP, and anti-WIP antibodies have been described (13,16,17). Anti-NHE-RF IC270 and anti-merlin antibodies 1C4 and C26H were described previously (18,19). Anti-Nck and anti-Myc 9E10 antibodies were purchased from BD Transduction Laboratories and Developmental Studies Hybridoma Bank, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Affinity-binding assays demonstrated that MED28 interacted with the SH3 domains of Grb2 (Wiederhold et al, 2004). Accordingly, MED28 was also named as magicin, merlin and Grb2 interacting cytoskeletal protein (Wiederhold et al, 2004).…”
Section: Descriptionmentioning
confidence: 99%
“…MED28 was also identified as a merlin-interacting protein by yeast two-hybrid screen (Wiederhold et al, 2004), where merlin, the neurofibromatosis 2 (NF2) tumor suppressor protein, belongs to the ezrin-radixinmoesin (ERM) family members. Affinity-binding assays demonstrated that MED28 interacted with the SH3 domains of Grb2 (Wiederhold et al, 2004).…”
Section: Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, understanding of the molecular biology and genetic mutations of NF2 has been increasing. 8,25,30,34,40 Drugs targeting the pathways involved in the molecular pathogenesis of NF2 are now under investigation. Potential treatments for NF2 are expected to emerge in the near future.…”
Section: Treatment For Children With Nf2mentioning
confidence: 99%